Review: The Use of Eco-Enzymes in Greywater Treatment - Khotimah, Siti Nurul; Ginting, Simparmin Br; Arifaini, Nur; Mardhotillah, Nur Anisa; Puligadda, Lohit Krishna Pranav (Journal of Engineering and Scientific Research, 2024)
Water pollution such as in rivers has become a concern due to its impact on health and the decreasing availability of clean water. There is a common assumption that industrial pollution is the main cause of water pollution. However, an interesting fact is that river pollution is largely dominated by contamination from household wastewater (domestic waste) discharged directly into drainage systems and ending up in rivers without prior treatment. Such cases are particularly prevalent in developing countries. Therefore, the challenge is to find solutions to treat domestic wastewater using simpler and cheaper technologies. Current research is focused on treating domestic wastewater especially greywater with eco-enzymes. Eco-enzymes are enzymes produced from the fermentation process of organic materials such as fruit peels or vegetable scraps for a minimum of three months. This paper will review the treatment of greywater using eco-enzymes, including the eco-enzyme production process, its characteristics, greywater characteristics, the methods employed, and the research findings. Finally, the paper will recommend possible avenues for further research related to the treatment of greywater using eco-enzymes